2016
DOI: 10.1111/jch.12850
|View full text |Cite
|
Sign up to set email alerts
|

Acute Sildenafil Use Reduces 24‐Hour Blood Pressure Levels in Patients With Resistant Hypertension: A Placebo‐Controlled, Crossover Trial

Abstract: The authors previously demonstrated that acute administration of sildenafil—a phosphodiesterase 5 (PDE5) inhibitor—improves hemodynamic parameters in patients with resistant hypertensive (RH), but its effect on ambulatory blood pressure monitoring (ABPM) is unknown. This interventional, nonrandomized, single‐blinded, placebo‐controlled, crossover trial included 26 patients with RH. A dose of sildenafil (187.5mg) was given, and after a washout period of 14 days the patients received a single oral dose of placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“… 26 Furthermore, sildenafil has demonstrated great therapeutic efficacy in addressing refractory hypertension, as evidenced by a clinical trial comprising 26 patients with refractory hypertension, which led to an 8.8 ± 1.4 mm Hg and 5.3 ± 3.3 mm Hg reduction in systolic and diastolic blood pressure, respectively. 27 The aforementioned findings indicated that Pde5 inhibitors may emerge as an innovative pharmacological approach for managing hypertension in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Furthermore, sildenafil has demonstrated great therapeutic efficacy in addressing refractory hypertension, as evidenced by a clinical trial comprising 26 patients with refractory hypertension, which led to an 8.8 ± 1.4 mm Hg and 5.3 ± 3.3 mm Hg reduction in systolic and diastolic blood pressure, respectively. 27 The aforementioned findings indicated that Pde5 inhibitors may emerge as an innovative pharmacological approach for managing hypertension in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps with repeated exposure to sildenafil, blood is ‘shunted’ away from the ocular circulation in favor of the systemic vasculature, resulting in compromised ocular blood flow and subsequent oxidative injury to the optic nerve head that may be a mechanism for the development or progression of glaucoma. Recent studies showing that acute sildenafil administration lowers blood pressure in a mouse model and in patients with resistant hypertension seem to support this possibility [ 24 , 25 ], although further work is necessary to clarify long-term effects.…”
Section: Discussionmentioning
confidence: 99%
“…Más aún, resultados obtenidos por Jackson y col. (Jackson, Benjamin et al 1999) en los primeros estudios clínicos de fase I en voluntarios sanos indicaron que SIL tiene modestas propiedades vasodilatadoras sin cambios significativos en la presión arterial. Por otro lado, se ha reportado un efecto hipotensor de SIL en pacientes con hipertensión resistente a 24 horas de la administración de una única dosis de SIL (Santa Catharina, Modolo et al 2016) por lo que tal vez tenga un efecto hipotensor transitorio en administración aguda y no en un tratamiento crónico como ocurre en nuestro caso. En efecto, en cuanto a su uso para el tratmiento de la hipertensión pulmonar, se ha reportado que SIL tiene una disminución significativa en la presión pulmonar sin afectar la presión arterial sistémica (Gillies, Roblin et al 2002).…”
Section: Sección Iv: Discusiónunclassified